Relação entre a diversidade de bactérias de produtos microbianos comerciais e seus efeitos sobre desempenho de cultivo do camarão marinho, litopenaeus vannamei - Lopes, Luiz Cayky da Silva (Universidade Federal Rural do Semi-Árido, 2021)
Probiotics are defined as live microorganisms that, administered in adequate amounts, promote health benefits to the host, favoring the intestinal microbial balance. The objective of this work was to evaluate the use of commercial probiotics with different bacterial compositions, in order to verify if there is a relationship between the diversity of bacteria used and their probiotic effects on the cultivation performance of the marine shrimp Litopenaeus vannamei. In a completely randomized design, the experiment was divided into 4 treatments with bacterial compounds with two, three and five different species of bacteria and 1 control, without the addition of probiotics. The shrimp were stored in water tanks of one thousand liters with densities of 150 shrimp/m², to observe the productive responses and the effect on water quality and on the control of nitrogen compounds. There were no significant differences (p>0.05) between treatments for average weight, weekly weight gain and feed conversion. It was observed that there was a reduction in NAT and nitrite in all treatments, including the control. It was observed that there was a reduction in NAT and nitrite in all treatments, including the control. Control survival was 96%, higher than all other treatments. Treatment P5b had the highest productivity 5417.8 kg/ha among all. The results of this experiment showed that bacterial diversity does not interfere with the production parameters or water quality in the cultivation of L. vannamei under the conditions presented here.
Keywords: Aquicultura; Produtos bacterianos; Camarão cultivado; Diversidade bacteriana; Bactérias probióticas; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA